2020
DOI: 10.3390/diagnostics10110882
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Characterization of Patellar Tendon in Non-Elite Sport Players with Painful Patellar Tendinopathy: Absolute Values or Relative Ratios? A Pilot Study

Abstract: Imaging findings in patellar tendinopathy are questioned. The aim of this pilot study was to characterize ultrasound measures, by calculating ultrasound ratio and neovascularization of the patellar tendon in non-elite sport players with unilateral painful patellar tendinopathy. Cross-sectional area (CSA), width, and thickness of the patellar tendon were assessed bilaterally in 20 non-elite sport-players with unilateral painful patellar tendinopathy and 20 asymptomatic controls by a blinded assessor. Ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Since PD activity is a common feature in PT and due to our inclusion criteria, we expected to find a greater area of neovascularization in the symptomatic tendon compared to the asymptomatic tendon. We used an in‐house, custom‐made macro to objectively quantify the total area (mm 2 ) affected by neovascularization, which is in contrast to most studies that have reported neovascularization by percentage or using the ordinal Öhberg score 17,27,33,34 . One study quantified neovascularization area (mm 2 ) in a comparable fashion to our study, and found considerably less PD (mean of ~2.0 mm 2 ) compared to our median of 25.6 mm 2 35 .…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Since PD activity is a common feature in PT and due to our inclusion criteria, we expected to find a greater area of neovascularization in the symptomatic tendon compared to the asymptomatic tendon. We used an in‐house, custom‐made macro to objectively quantify the total area (mm 2 ) affected by neovascularization, which is in contrast to most studies that have reported neovascularization by percentage or using the ordinal Öhberg score 17,27,33,34 . One study quantified neovascularization area (mm 2 ) in a comparable fashion to our study, and found considerably less PD (mean of ~2.0 mm 2 ) compared to our median of 25.6 mm 2 35 .…”
Section: Discussionmentioning
confidence: 56%
“…PD is a common feature of PT, 17,31,32 although studies have also reported a lack of PD activity in symptomatic PT. 17,27,32 Since PD activity is a common feature in PT and due to our inclusion criteria, we expected to find a greater area of neovascularization in the symptomatic tendon compared to the asymptomatic tendon. We used an inhouse, custom-made macro to objectively quantify the total area (mm 2 ) affected by neovascularization, which is in contrast to most studies that have reported neovascularization by percentage or using the ordinal Öhberg score.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations